Nanocarriers for anticancer drugs--new trends in nanomedicine - Drbohlavova, Jana; Chomoucka, Jana; Adam, Vojtech; Ryvolova, Marketa; Eckschlager, Tomas; Hubalek, Jaromir; Kizek, Rene (Current drug metabolism, 2013)
This review provides a brief overview of the variety of carriers employed for targeted drug delivery used in cancer therapy and summarizes advantages and disadvantages of each approach. Particularly, the attention was paid to polymeric nanocarriers, liposomes, micelles, polyethylene glycol, poly(lactic-co-glycolic acid), dendrimers, gold and magnetic nanoparticles, quantum dots, silica nanoparticles, and carbon nanotubes. Further, this paper briefly focuses on several anticancer agents (paclitaxel, docetaxel, camptothecin, doxorubicin, daunorubicin, cisplatin, curcumin, and geldanamycin) and on the influence of their combination with nanoparticulate transporters to their properties such as cytotoxicity, short life time and/or solubility.
Keywords: nanomedicína; Nanoparticles; Nanotechnology; Humans; Drug Carriers; Nanomedicine; Antineoplastic Agents; rozpustnost; nanotechnologie; Drug Delivery Systems; lidé; zvířata; Drug Design; lékové transportní systémy; Neoplasms; racionální návrh léčiv; nanočástice; nosiče léků; Solubility; protinádorové látky; nádory; Animals